The MADS-box gene EjAGL15 positively regulates lignin deposition in the flesh of loquat fruit during its storage - Ge, Hang; Xu, Hongxia; Li, Xiaoying; Chen, Junwei (Frontiers in Plant Science, 2023)
Lignification of fruit flesh is a common physiological disorder that occurs during post-harvest storage, resulting in the deterioration of fruit quality. Lignin deposition in loquat fruit flesh occurs due to chilling injury or senescence, at temperatures around 0°C or 20°C, respectively. Despite extensive research on the molecular mechanisms underlying chilling-induced lignification, the key genes responsible for the lignification process during senescence in loquat fruit remain unknown. MADS-box genes, an evolutionarily conserved transcription factor family, have been suggested to play a role in regulating senescence. However, it is still unclear whether MADS-box genes can regulate the lignin deposition that arises from fruit senescence. A loquat MADS-box gene was recently identified as a negative regulator of lignin biosynthesis that is induced only in response to chilling injury. This finding raises the hypothesis that lignification triggered by chilling and senescence may be under the control of different MADS-box genes. In this study, we simulated both senescence- and chilling-induced flesh lignification by applying temperature treatments. The lignin content of the flesh samples treated at 20°C or 0°C increased during storage, but at different rates. Results from transcriptome analysis, quantitative reverse transcription PCR, and correlation analysis led us to identify a senescence-specific MADS-box gene, EjAGL15, which correlated positively with the variation in lignin content of loquat fruit. Luciferase assay results confirmed that EjAGL15 activated multiple lignin biosynthesis-related genes. Our findings suggest that EjAGL15 functions as a positive regulator of senescence-induced flesh lignification in loquat fruit.